A kind of iron-chromium-cobalt alloy and its deformation processing technology

By adding tungsten and rare earth oxides to the iron-chromium cobalt alloy and adopting multi-step process treatment, the problem of coercive force attenuation in traditional alloys at high or low temperatures is solved, and the magnetic performance and stability of the alloy are improved.

CN119753519APending Publication Date: 2025-04-04HANGZHOU KEXING MAGNETIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510050614.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional iron-chromium cobalt alloys have a significant attenuation of coercive forces in high or low temperature environments, affecting the stability and performance of magnetic materials.

Method used

By adding a mixture of tungsten and rare earth element oxides to the iron-chromium cobalt alloy, the microstructure and magnetic properties of the alloy are optimized.

Benefits of technology

It effectively maintains the stability of coercive force, improves the magnetic performance stability of the alloy when temperature changes, reduces hysteresis loss, enhances corrosion resistance and structural stability, and meets the stability requirements of magnetic materials at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753519A_ABST
    Figure CN119753519A_ABST
Patent Text Reader

Abstract

The invention relates to the field of iron-chromium-cobalt alloys, and discloses an iron-chromium-cobalt alloy and a deformation processing technology thereof. The iron-chromium-cobalt alloy comprises the following raw materials by weight: 50-55 parts of iron, 28-30 parts of chromium, 10-12 parts of cobalt, 2-3 parts of molybdenum, 1-1.2 parts of titanium, 3-5 parts of tungsten, 1.5-2.5 parts of niobium, 1-2 parts of aluminum, and 0.5-1 parts of a rare earth element oxide mixture. The dispersed phase formed by the tungsten element can act as a pinning point to hinder the movement of the magnetic domain wall, and help maintain the stability of the coercive force during the temperature change process. The neodymium oxide in the rare earth element oxide mixture can also improve the magnetic domain structure and magnetocrystalline anisotropy, and has a positive effect on stabilizing the coercive force. At the same time, through the synergy of other elements, the coercive force of the alloy can remain relatively stable when the temperature changes, thereby solving the problem that the coercive force of the traditional iron-chromium-cobalt alloy is greatly attenuated in a high or low temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of iron-chromium-cobalt alloys, in particular to an iron-chromium-cobalt alloy and a deformation processing technology thereof. Background Art

[0002] As a key magnetic material, Fe-Cr-Co alloy has long played an indispensable role in many important fields such as electroacoustics, instrumentation, medical treatment, aerospace, etc. In the electroacoustic field, it is widely used in audio equipment such as speakers and headphones, responsible for accurately converting electrical signals into high-quality sound signals, thereby bringing users a clear and realistic auditory experience; in terms of instrumentation, equipment such as various precision measuring instruments, sensors, and hysteresis motors rely on the magnetic properties of Fe-Cr-Co alloy to achieve accurate measurement, stable operation, and efficient energy conversion, providing reliable data support for industrial production and scientific research; in the aerospace field, it is used in aircraft engine control systems, satellite attitude adjustment devices, and various electronic equipment. With its stable magnetic properties, it ensures the normal operation of aerospace equipment and the smooth execution of key tasks under extreme space environments and complex aviation conditions.

[0003] With the rapid development of science and technology, electronic devices are constantly moving towards miniaturization, high performance and high stability. This requires magnetic materials to maintain stable and excellent magnetic properties over a wider temperature range. The coercivity of iron-chromium-cobalt alloys changes with temperature. When the temperature rises, the coercivity usually decreases. This is because the increase in temperature weakens the pinning effect of the magnetic domain wall, making it easier for the magnetic domain to flip. In magnetic storage devices and some magnetic elements with memory functions, the stability of the coercivity is crucial for the accurate storage and reading of signals. If the coercivity decreases, the stored magnetic information will be accidentally erased when it is not needed or new information will be written incorrectly, affecting the accuracy and stability of the data. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an iron-chromium-cobalt alloy and a deformation processing technology thereof, which solves the problem that the coercive force of the traditional iron-chromium-cobalt alloy is greatly attenuated in a high or low temperature environment.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: an iron-chromium-cobalt alloy, comprising the following raw materials in parts by weight: 50-55 parts of iron, 28-30 parts of chromium, 10-12 parts of cobalt, 2-3 parts of molybdenum, 1-1.2 parts of titanium, 3-5 parts of tungsten, 1.5-2.5 parts of niobium, 1-2 parts of aluminum, and 0.5-1 part of a mixture of rare earth element oxides.

[0006] Preferably, the rare earth element oxide mixture includes lanthanum oxide, cerium oxide and neodymium oxide, and the weight ratios thereof are 0.5-1.5:1.5-2.5:0.5-1.5, respectively, and the purity is not less than 99%.

[0007] Preferably, the average particle size of the rare earth element oxide mixture is less than 50 μm.

[0008] A deformation processing technology of iron-chromium-cobalt alloy comprises the following steps: S1. Alloying: mechanically alloying a mixture of iron, chromium, cobalt, molybdenum, titanium, tungsten, niobium, aluminum and rare earth element oxides by weight through a ball mill to obtain an alloy raw material; S2. Melting and casting: Melting the alloy raw materials in a vacuum induction furnace, stirring with an electromagnetic stirring device during the melting process, and casting to form an ingot after the melting is completed; S3, homogenization treatment: placing the ingot in a high temperature resistance furnace for homogenization treatment, the atmosphere in the furnace is high purity argon; S4, hot extrusion: the ingot after homogenization treatment is subjected to hot extrusion deformation through a hot extrusion die on a hydraulic press to obtain a billet; S5, Annealing: The blank is annealed online in a continuous annealing furnace, and a segmented temperature control method is adopted in the furnace; S6, cold working: the blank is subjected to cold working deformation by a numerically controlled rolling mill, and preferably, emulsion cooling and lubrication are used during the rolling process. The ball-to-material ratio of the mechanical alloying by the ball mill in S1 is controlled at 8:1-12:1, the ball milling time is 12-18 hours, and the rotation speed is 250-350r / min.

[0009] Preferably, the smelting temperature in S2 is 1400° C.-1500° C., the smelting time is 2-3 hours, and the stirring rate is 100-300 r / min.

[0010] Preferably, the temperature for the homogenization treatment in S3 is 950° C.-1050° C., the heat preservation time is 4-6 hours, and then air cooling is performed.

[0011] Preferably, the temperature for hot extrusion deformation in S4 is 750° C.-850° C., the extrusion ratio is 4-6, and the extrusion speed is 50-80 mm / s.

[0012] Preferably, the annealing temperature of the online annealing treatment in S5 is 600° C.-700° C., the holding time is 1-2 hours, and the annealing is carried out with the furnace cooling.

[0013] Preferably, the deformation amount of the cold working deformation in S6 is controlled within a range of 25%-40%.

[0014] The present invention provides an iron-chromium-cobalt alloy and a deformation processing technology thereof, which has the following beneficial effects: 1. The dispersed phase formed by tungsten in the present invention can act as a pinning point to hinder the movement of the magnetic domain wall, which helps to maintain the stability of the coercive force during temperature changes. The neodymium oxide in the rare earth element oxide mixture can also improve the magnetic domain structure and magnetocrystalline anisotropy, which has a positive effect on stabilizing the coercive force. At the same time, through the synergy of other elements, the coercive force of the alloy can remain relatively stable when the temperature changes, thereby solving the problem of significant attenuation of the coercive force of traditional iron-chromium-cobalt alloys in high or low temperature environments.

[0015] 2. The present invention optimizes the magnetic domain structure of the alloy under the joint action of the rare earth element oxide mixture and other alloy elements, and the hysteresis loss can be maintained at a low level at different temperatures, so that the performance of the alloy in the alternating magnetic field is better, and the signal transmission accuracy and stability problems caused by the fluctuation of hysteresis performance can be effectively avoided, meeting the application scenarios with high requirements for hysteresis performance.

[0016] 3. The present invention improves the corrosion resistance and structural stability of the alloy by appropriately reducing the cobalt content and increasing the chromium content while ensuring certain magnetic properties. The reasonable combination of elements such as molybdenum, titanium, tungsten, niobium and aluminum synergistically improves the strength, hardness, thermal stability and hysteresis properties of the alloy through mechanisms such as grain refinement, dispersion strengthening and the formation of stable compounds.

[0017] 4. The present invention improves the anti-oxidation performance of the alloy through lanthanum oxide, prolongs the service life of the alloy, and enables it to work in a more severe oxidizing environment. Cerium oxide plays a role in deoxidation and desulfurization, purifies the alloy liquid, reduces the adverse effects of impurity elements on the performance of the alloy, and improves the quality and performance stability of the alloy. Neodymium oxide improves the magnetic properties of the alloy, and improves the magnetic permeability and coercive force of the alloy by optimizing the magnetic domain structure and magnetocrystalline anisotropy, thereby enhancing the responsiveness of the alloy in a magnetic field.

[0018] 5. The present invention achieves excellent microstructure and performance of the alloy through the synergistic effect of various process steps, such as refined grains, uniform component distribution, good hysteresis performance and coercive force temperature stability, and improves the problems of high energy consumption, serious environmental pollution and high cost brought about by the traditional high-temperature solid solution process. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention provides a process flow chart of an iron-chromium-cobalt alloy deformation processing technology. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example: An embodiment of the present invention provides an iron-chromium-cobalt alloy, comprising the following raw materials in parts by weight: 50-55 parts of iron, 28-30 parts of chromium, 10-12 parts of cobalt, 2-3 parts of molybdenum, 1-1.2 parts of titanium, 3-5 parts of tungsten, 1.5-2.5 parts of niobium, 1-2 parts of aluminum, and 0.5-1 part of a mixture of rare earth element oxides.

[0022] Specifically, the addition of iron provides a basic structural framework for the alloy, ensuring that the alloy has a certain toughness and plasticity, allowing other elements to be evenly dispersed in it, thereby achieving balance and stability in the overall performance of the alloy, laying the foundation for subsequent various strengthening mechanisms and performance optimizations.

[0023] The addition of chromium improves the corrosion resistance of the alloy. By forming a dense oxide film on the surface of the alloy, the external environment can be effectively prevented from corroding the alloy, so that the alloy can maintain stable performance in various complex use environments (such as moisture, acid, alkali and other media), thereby broadening the application range of the alloy. At the same time, the chromium element also helps to stabilize the crystal structure of the alloy, providing a certain structural basis for improving magnetic properties and thermal stability.

[0024] The addition of cobalt helps to improve the alloy's saturation magnetic induction intensity and Curie point, enhance the alloy's magnetic properties, and enable it to exhibit better response characteristics in a magnetic field environment. For example, it can more effectively achieve energy conversion and transmission in applications such as motors and electromagnetic equipment, thereby improving the alloy's performance in magnetic-related applications.

[0025] The addition of molybdenum can refine the grains. During the solidification and heat treatment of the alloy, molybdenum atoms will be concentrated at the grain boundaries, hindering the growth of the grains and making the grain structure of the alloy more uniform and fine, which is beneficial to improving the strength and hardness of the alloy. It can also improve the processing performance of the alloy, making the alloy easier to form in subsequent cold and hot processing. At the same time, the uniform and fine grain structure also has a certain promoting effect on the stability of the magnetic properties.

[0026] By adding titanium, stable compounds are formed with other elements in the alloy (such as chromium, molybdenum, etc.). These compounds are distributed in a fine dispersed state inside the alloy, playing a role of dispersion strengthening, which can improve the strength and hardness of the alloy, and also enhance the stability of the alloy at high temperatures, so that the alloy can still maintain good performance when subjected to greater mechanical stress and high temperature environment, and also has a certain optimization effect on the hysteresis properties of the alloy, so that it can work more stably in an alternating magnetic field environment.

[0027] By adding tungsten, due to the incomplete dissolution of tungsten in iron, hard and brittle ε phases will be generated. These ε phases are dispersed in the alloy and can act as pinning points. Therefore, during the change of the magnetic field, the pinning points can effectively hinder the movement of the magnetic domain wall, thereby greatly improving the coercive force of the alloy. When the temperature changes, it can help maintain the stability of the coercive force, so that the alloy can maintain stable magnetic properties in a wide temperature range and is suitable for more complex working temperature environments. By adding niobium, it can combine with impurity elements such as carbon and nitrogen in the alloy to form fine carbide and nitride particles. These particles are evenly distributed at the grain boundaries and inside the grains, which play a role in refining the grains and inhibiting grain growth, further improving the high temperature strength and thermal stability of the alloy. At the same time, the presence of niobium can also enhance the grain refining effect of molybdenum, and synergize with other elements to optimize the microstructure of the alloy, thereby improving the comprehensive performance and service life of the alloy.

[0028] The addition of aluminum can affect the growth morphology of crystals during the solidification process of the alloy, promoting the formation of a more uniform and dense microstructure. Aluminum can also undergo certain chemical reactions with other elements to generate some strengthening phases, further improving the strength and hardness of the alloy. In addition, the presence of aluminum helps to adjust the phase structure of the alloy and optimize the overall performance of the alloy, thereby improving both its mechanical and magnetic properties and improving the quality and reliability of the alloy.

[0029] By adding a mixture of rare earth element oxides, the alloy has a synergistic effect of anti-oxidation, purification and magnetic property optimization, giving full play to the unique advantages of rare earth elements, further optimizing the microstructure and properties of the alloy, improving the comprehensive performance of the alloy, and making it more competitive in the market.

[0030] Through the synergistic effect of various raw materials in the alloy and the cooperation of various elements, the quality of the alloy is comprehensively improved from microstructure to macroscopic performance, which makes up for the shortcomings of traditional iron-chromium-cobalt alloy in performance. Thus, the temperature stability of coercive force is improved while taking into account the hysteresis performance. At the same time, the comprehensive performance indicators such as mechanical properties, corrosion resistance, oxidation resistance and processing performance of the alloy are optimized, and the application field and scope of the alloy are expanded, so that it can meet the diversified and strict requirements of modern industry for high-performance magnetic materials, and improve the market competitiveness and added value of the products.

[0031] The rare earth element oxide mixture includes lanthanum oxide, cerium oxide and neodymium oxide, and the weight ratios thereof are 0.5-1.5:1.5-2.5:0.5-1.5, respectively, and the purity is not less than 99%; the average particle size of the rare earth element oxide mixture is less than 50 μm.

[0032] Specifically, by adding lanthanum oxide, the oxidation resistance of the alloy is improved, and by forming a more stable oxide protective film on the surface of the alloy, oxygen is prevented from further invading the interior of the alloy, thereby extending the service life of the alloy.

[0033] Cerium oxide has good deoxidation and desulfurization capabilities. The addition of cerium oxide can purify the alloy liquid, reduce the adverse effects of impurity elements on the alloy properties, make the alloy composition purer, the performance more stable, and improve the quality and reliability of the alloy.

[0034] By adding neodymium oxide, the magnetic properties of the alloy are improved. By affecting the magnetic domain structure and magnetocrystalline anisotropy, the magnetic permeability and coercive force of the alloy are increased, and the performance of the alloy in a magnetic field is enhanced, giving it better application prospects in the fields of electromagnetic equipment.

[0035] Please see attached Figure 1 , a Fe-Cr-Co alloy deformation processing process, comprising the following steps: S1. Alloying: Mechanically alloying a mixture of iron, chromium, cobalt, molybdenum, titanium, tungsten, niobium, aluminum and rare earth element oxides by weight through a ball mill to obtain an alloy raw material; in S1, the ball-to-material ratio of the mechanical alloying through the ball mill is controlled at 8:1-12:1, the ball milling time is 12-18 hours, and the rotation speed is 250-350r / min.

[0036] Specifically, the alloy raw material is obtained by mechanically alloying a mixture of iron, chromium, cobalt, molybdenum, titanium, tungsten, niobium, aluminum and rare earth element oxides by weight through a ball mill, so that various elements are fully mixed and diffused under the action of high-energy ball milling to form a uniform alloy powder, which lays a foundation for forming an alloy ingot with uniform composition in the subsequent smelting process, ensures the consistency and stability of the alloy performance, and improves the quality reliability of the alloy. At the same time, the cold working effect in the mechanical alloying process also helps to refine the grains of the alloy powder, creating favorable conditions for subsequent processing and performance improvement.

[0037] S2. Melting and casting: the alloy raw materials are melted in a vacuum induction furnace, and an electromagnetic stirring device is used for stirring during the melting process. After the melting is completed, the alloy raw materials are cast to form an ingot. The melting temperature in S2 is 1400°C-1500°C, the melting time is 2-3 hours, and the stirring rate is 100-300r / min.

[0038] Specifically, the alloy raw materials are smelted in a vacuum induction furnace, stirred by an electromagnetic stirring device during the smelting process, and cast to form ingots after the smelting is completed, so that the alloy raw materials are fully melted and mixed evenly in a high-temperature liquid state. The electromagnetic stirring further ensures the uniformity of the alloy composition and avoids the occurrence of local component segregation. Smelting under a vacuum environment can reduce the gas impurity content in the alloy and improve the purity and quality of the alloy. After the smelting is completed, it is cast to form ingots to obtain an alloy blank with a certain shape and size, which provides a basic material for subsequent processing.

[0039] S3, homogenization treatment: the ingot is placed in a high temperature resistance furnace for homogenization treatment, and the atmosphere in the furnace is high purity argon gas; the temperature for homogenization treatment in S3 is 950°C-1050°C, and the insulation time is 4-6 hours, followed by air cooling.

[0040] Specifically, the ingot is placed in a high-temperature resistance furnace for homogenization treatment, and the atmosphere in the furnace is high-purity argon, so that the composition inside the ingot is further homogenized, eliminating the component segregation caused by the solidification process. At the same time, the ingot is treated in a high-purity argon atmosphere to prevent oxidation at high temperatures, thereby ensuring the surface quality of the alloy and the stability of the internal organization. The ingot after homogenization treatment has a more uniform and consistent organizational structure and properties, providing a good blank for subsequent hot extrusion and other processing processes, improving the overall performance and processing performance of the alloy, and reducing the scrap rate during the processing.

[0041] S4, hot extrusion: the ingot after homogenization treatment is hot extruded and deformed through a hot extrusion die on a hydraulic press to obtain a billet; the temperature of the hot extrusion deformation in S4 is 750°C-850°C, the extrusion ratio is 4-6, and the extrusion speed is 50-80mm / s.

[0042] Specifically, the ingot after homogenization treatment is subjected to hot extrusion deformation through a hot extrusion die on a hydraulic press to obtain a blank, and during the hot extrusion process, the ingot is plastically deformed under the action of high temperature and pressure, which further refines the grains of the alloy and makes the structure denser. At the same time, the streamline distribution of the alloy is improved, and the mechanical properties (such as strength, hardness, toughness, etc.) and isotropy of the alloy are improved. In addition, hot extrusion can make the shape of the alloy closer to the shape of the final product, reduce the workload of subsequent processing, improve production efficiency, and enable the alloy to meet higher requirements for industrial applications.

[0043] S5, annealing: the blank is annealed online in a continuous annealing furnace, and a segmented temperature control method is adopted in the furnace; the annealing temperature of the online annealing treatment in S5 is 600℃-700℃, the holding time is 1-2 hours, and the blank is cooled with the furnace.

[0044] Specifically, the billet is annealed online in a continuous annealing furnace, and a segmented temperature control method is adopted in the furnace, so as to eliminate the internal stress generated during the hot extrusion process, stabilize the organizational structure and performance of the alloy, and prevent defects such as alloy deformation and cracking caused by internal stress. At the same time, the segmented temperature control method can more accurately control the organizational structure transformation of the alloy, further optimize the performance of the alloy, such as improving the plasticity and toughness of the alloy, improving the processing performance of the alloy, providing good conditions for subsequent cold processing, and ensuring the reliability and stability of the alloy in subsequent processing and use.

[0045] S6, cold working: the blank is subjected to cold working deformation by a numerically controlled rolling mill, and emulsion cooling and lubrication are used during the rolling process; the deformation amount of the cold working deformation in S6 is controlled within 25%-40%.

[0046] Specifically, by subjecting the billet to cold working deformation through a CNC rolling mill and using emulsion cooling and lubrication during the rolling process, the strength and hardness of the alloy can be further improved, and the mechanical properties of the alloy can be further improved through the work hardening effect. At the same time, emulsion cooling and lubrication can reduce friction and heat generation during the rolling process, prevent oxidation and burning of the alloy surface, ensure the surface quality and dimensional accuracy of the alloy, and enable the alloy to ultimately achieve the desired shape and performance requirements, thereby producing high-quality iron-chromium-cobalt alloy products to meet the market demand for high-performance iron-chromium-cobalt alloys.

[0047] Through the coordinated implementation of various steps, the organizational structure and properties of the alloy can be precisely controlled and optimized, from the uniform mixing of raw materials to the forming of ingots, and then to the gradual improvement of the microstructure and macroscopic properties of the alloy through hot and cold working. Together, we can create an iron-chromium-cobalt alloy product with excellent performance and stability, ensure the feasibility and sustainability of the alloy in industrial production, promote technological progress and industrial upgrading in the field of magnetic materials, and meet the growing market demand and the urgent need of high-end manufacturing for high-performance magnetic materials.

[0048] The following is further introduced in conjunction with specific embodiments: Embodiment 1: An iron-chromium-cobalt alloy comprises the following raw materials in parts by weight: 55 parts of iron, 30 parts of chromium, 12 parts of cobalt, 3 parts of titanium, 1.2 parts of titanium, 5 parts of tungsten, 2.5 parts of niobium, 2 parts of aluminum, and 1 part of a rare earth element oxide mixture.

[0049] The rare earth element oxide mixture includes lanthanum oxide, cerium oxide and neodymium oxide, and the weight ratio thereof is 1:2:1, respectively, and the purity is not less than 99%.

[0050] The average particle size of the rare earth element oxide mixture is less than 50 μm.

[0051] A deformation processing technology of iron-chromium-cobalt alloy comprises the following steps: S1. Alloying: mechanically alloying a mixture of iron, chromium, cobalt, molybdenum, titanium, tungsten, niobium, aluminum and rare earth element oxides by weight through a ball mill to obtain an alloy raw material; S2. Melting and casting: Melting the alloy raw materials in a vacuum induction furnace, stirring with an electromagnetic stirring device during the melting process, and casting to form an ingot after the melting is completed; S3, homogenization treatment: placing the ingot in a high temperature resistance furnace for homogenization treatment, the atmosphere in the furnace is high purity argon; S4, hot extrusion: the ingot after homogenization treatment is subjected to hot extrusion deformation through a hot extrusion die on a hydraulic press to obtain a billet; S5, Annealing: The blank is annealed online in a continuous annealing furnace, and a segmented temperature control method is adopted in the furnace; S6. Cold working: The blank is cold-worked and deformed by a CNC rolling mill, and emulsion cooling and lubrication are used during the rolling process.

[0052] In S1, the ball-to-material ratio for mechanical alloying by ball milling was controlled at 10:1, the ball milling time was 15 hours, and the rotation speed was 300 r / min.

[0053] The smelting temperature in S2 is 1450° C., the smelting time is 2.5 hours, and the stirring rate is 200 r / min.

[0054] The temperature for the homogenization treatment in S3 is 1000° C., and the heat preservation time is 5 hours, followed by air cooling.

[0055] The temperature for hot extrusion deformation in S4 is 800°C, the extrusion ratio is 5, and the extrusion speed is 65 mm / s.

[0056] The annealing temperature for the online annealing treatment in S5 is 650° C., the holding time is 2 hours, and the furnace is cooled.

[0057] The amount of cold working deformation in S6 is controlled to be 30%.

[0058] Embodiment 2: The difference between this embodiment and the above-mentioned embodiment 1 is that: An iron-chromium-cobalt alloy comprises the following raw materials in parts by weight: 50 parts of iron, 28 parts of chromium, 10 parts of cobalt, 2 parts of molybdenum, 1 part of titanium, 3 parts of tungsten, 1.5 parts of niobium, 1 part of aluminum, and 0.5 parts of a rare earth element oxide mixture.

[0059] Embodiment 3: The difference between this embodiment and the above-mentioned embodiment 1 is that: An iron-chromium-cobalt alloy comprises the following raw materials in parts by weight: 52.5 parts of iron, 29 parts of chromium, 11 parts of cobalt, 2.5 parts of molybdenum, 1.1 parts of titanium, 4 parts of tungsten, 2 parts of niobium, 1.5 parts of aluminum, and 0.75 parts of a rare earth element oxide mixture.

[0060] Table 1: contrast Example 1 Example 2 Example 3 Standard value Coercivity temperature coefficient (% / ℃) -0.005 -0.006 -0.0055 -0.0128 Coercive force (kA / m) ≤55 ≤50 ≤52 ≤44 The above table compares the traditional iron-chromium-cobalt alloy. From Table 1, it can be seen that different amounts of iron, chromium, cobalt, molybdenum, titanium, tungsten, niobium, aluminum, and rare earth element oxide mixtures can affect the coercive force temperature coefficient and coercive force of the iron-chromium-cobalt alloy, and then affect the magnetic domain structure and microstructure of the iron-chromium-cobalt alloy, thereby enhancing the thermal stability and magnetic stability of the iron-chromium-cobalt alloy, so that the coercive force of the alloy can remain relatively stable when the temperature changes, thereby solving the problem of the traditional iron-chromium-cobalt alloy having a significant attenuation of coercive force in high or low temperature environments.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An iron-chromium-cobalt alloy, characterized in that: The invention comprises the following raw materials in parts by weight: 50-55 parts of iron, 28-30 parts of chromium, 10-12 parts of cobalt, 2-3 parts of molybdenum, 1-1.2 parts of titanium, 3-5 parts of tungsten, 1.5-2.5 parts of niobium, 1-2 parts of aluminum and 0.5-1 parts of a mixture of rare earth element oxides.

2. The iron-chromium-cobalt alloy according to claim 1, characterized in that: The rare earth element oxide mixture includes lanthanum oxide, cerium oxide and neodymium oxide, and the weight ratios thereof are 0.5-1.5:1.5-2.5:0.5-1.5, respectively, and the purity is not less than 99%.

3. The iron-chromium-cobalt alloy according to claim 1, characterized in that: The average particle size of the rare earth element oxide mixture is less than 50 μm.

4. A deformation processing technology of iron-chromium-cobalt alloy, characterized by: An iron-chromium-cobalt alloy applied to any one of claims 1 to 3, comprising the following steps: S1. Alloying: mechanically alloying a mixture of iron, chromium, cobalt, molybdenum, titanium, tungsten, niobium, aluminum and rare earth element oxides by weight through a ball mill to obtain an alloy raw material; S2. Melting and casting: Melting the alloy raw materials in a vacuum induction furnace, stirring with an electromagnetic stirring device during the melting process, and casting to form an ingot after the melting is completed; S3, homogenization treatment: placing the ingot in a high temperature resistance furnace for homogenization treatment, the atmosphere in the furnace is high purity argon; S4, hot extrusion: the ingot after homogenization treatment is subjected to hot extrusion deformation through a hot extrusion die on a hydraulic press to obtain a billet; S5, Annealing: The blank is annealed online in a continuous annealing furnace, and a segmented temperature control method is adopted in the furnace; S6. Cold working: The blank is cold-worked and deformed by a CNC rolling mill, and emulsion cooling and lubrication are used during the rolling process.

5. The iron-chromium-cobalt alloy deformation processing process according to claim 4, characterized in that: In the S1, the ball-to-material ratio for mechanical alloying by ball mill is controlled at 8:1-12:1, the ball milling time is 12-18 hours, and the rotation speed is 250-350 r / min.

6. The Fe-Cr-Co alloy deformation processing process according to claim 4, characterized in that: The smelting temperature in S2 is 1400° C.-1500° C., the smelting time is 2-3 hours, and the stirring rate is 100-300 r / min.

7. The Fe-Cr-Co alloy deformation processing process according to claim 4, characterized in that: The temperature of the homogenization treatment in S3 is 950° C.-1050° C., and the heat preservation time is 4-6 hours, followed by air cooling.

8. The Fe-Cr-Co alloy deformation processing process according to claim 4, characterized in that: The temperature for hot extrusion deformation in S4 is 750° C.-850° C., the extrusion ratio is 4-6, and the extrusion speed is 50-80 mm / s.

9. The iron-chromium-cobalt alloy deformation processing process according to claim 4, characterized in that: The annealing temperature of the online annealing treatment in S5 is 600° C.-700° C., the heat preservation time is 1-2 hours, and the furnace is cooled.

10. The Fe-Cr-Co alloy deformation processing process according to claim 4, characterized in that: The amount of cold working deformation in S6 is controlled to be 25%-40%.